Strategies for survival at Sibikwa 1988-2021
1 online resource (xii, 273 pages)
Keywords: "This book provides an engaging and contextualised insight into a South African township-based arts centre that has survived the vicissitudes of steady militarisation in townships during some of the worst years of apartheid as well as the exhilaration of a new democratic polity while attempting to circumnavigate different policies and funding dispensations. Sibikwa provides arts centres across the world and especially those in decolonising countries with strategies for survival in tumultuous times. This multi-disciplinary book maps and co-ordinates wider historical, political, and social contextual concerns and events with matters specific to a community-based east of Johannesburg and provides an exploration and analysis by experts of authentic theatre-making and performance, dance, indigenous music, arts in education and NGO governance. It has contemporary significance and raises important questions regarding inclusivity and transformation, the function and future of arts centres, community-based applied arts practices, creativity, and international partnerships. This study will be of great interest to students and scholars in theatre and performance, indigenous music, dance, and South African history"--